Production Economics and Determinants of Potato Production in Nuwakot, Nepal - Dahal, Bhishma Raj; Rijal, Swodesh (International Journal of Applied Sciences and Biotechnology, 2019)
A study was conducted for comparative analysis of demographic, production economics and determinants of potato production between Kakani rural municipality and Bidur municipality of Nuwakot district. Altogether 120 potato producers, 56 from Kakani and 64 from Bidur were randomly selected. Pretested semi-structured questionnaire was administered to randomly selected farmers. Potato growers were interviewed using face to face interview method in the month of October 2018. All the data were entered into SPSS and Microsoft excel and analysis was done by using Microsoft excel, STATA and SPSS. Average productivity in the research area was 14.69 ton per hectare. Average cost of production and profit was Rs 8614.61 per ropani and Rs 6083 per ropani respectively. B/C ratio in the research area was 1.71. 10% increase in organic manure (FYM and poultry manure), pesticide and tuber resulted in 1.88%, 1.99% and 0.05% increase in income respectively. 10% increase in labor and chemical fertilizer resulted into 0.1% and 0.5% decrease in output. Labor and chemical fertilizer was over utilized resource for potato production. The probability of cultivation of potato in large scale was found to be 56.92% higher for those with access to extensive service and 47.89% higher for those who have received training. Most of the farmers don not use improved seed thus distributing improved seed, providing training and extension services help to increase profit of potato production in Nuwakot district. 100% increase in all the factor of production would result in 32.39% increase in potato production. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 62-68